2018
DOI: 10.1080/00223891.2018.1465431
|View full text |Cite
|
Sign up to set email alerts
|

Criterion A of the AMPD in HiTOP

Abstract: The categorical model of personality disorder classification in the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (5th ed. [DSM-5]; American Psychiatric Association, 2013 ) is highly and fundamentally problematic. Proposed for DSM-5 and provided within Section III (for Emerging Measures and Models) was the Alternative Model of Personality Disorder (AMPD) classification, consisting of Criterion A (self-interpersonal deficits) and Criterion B (maladaptive personality tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 66 publications
10
113
1
2
Order By: Relevance
“…Our finding of two latent subdomains, resembling components of self‐ and interpersonal dysfunction, is consistent with the ecumenical approach to conceptualizing personality pathology proposed by Bender . Accordingly, this structure supports previous empirical research on the DSM‐5 AMPD framework of self/other functioning . Our finding is particularly consistent with previous research on self‐reported personality dysfunction in Danish psychiatric patients and incarcerated addicts as well as Dutch psychiatric patients .…”
Section: Discussionsupporting
confidence: 91%
“…Our finding of two latent subdomains, resembling components of self‐ and interpersonal dysfunction, is consistent with the ecumenical approach to conceptualizing personality pathology proposed by Bender . Accordingly, this structure supports previous empirical research on the DSM‐5 AMPD framework of self/other functioning . Our finding is particularly consistent with previous research on self‐reported personality dysfunction in Danish psychiatric patients and incarcerated addicts as well as Dutch psychiatric patients .…”
Section: Discussionsupporting
confidence: 91%
“…disinhibited eternalizing includes substance use disorders and internalizing includes mood and anxiety disorders), and there has been much debate regarding what constitutes general personality functioning vs. personality pathology. 26,40 A discussion of this distinction is beyond the scope of the current work as the literature is equivocal. Additionally, given that research specific to the HiTOP model is sparse, evidence for the HiTOP approach to treatment is extrapolated from existing evidence with related models and therefore should be considered speculative.…”
Section: Hierarchical Taxonomy Of Psychopathologymentioning
confidence: 97%
“…There are a few recent notable HiTOP papers beyond the current issue of Personality and Mental Health that are particularly relevant to the current manuscript. Widiger et al 40 describe the potential role, importance and implications of personality within the HiTOP dimensional model of psychopathology, Hopwood et al 27 focus on specific potential advantages of HiTOP for psychotherapy research and practice, and Ruggero et al 41 outline general issues involved in translating HiTOP to clinical practice. The goal of the current paper is to integrate these three areas to highlight potential psychotherapeutic and pharmacological treatment technique recommendations for personality pathology specifically defined within the HiTOP model.…”
Section: Hierarchical Taxonomy Of Psychopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The DSM‐IV and ICD‐10 took a more medical approach to psychopathology, which suggested that personality disorders were categorical constructs rather than dimensional ones. The authors of the newest versions of DSM‐5 and ICD‐11 began shifting the understanding of personality disorder from classification towards dimensions (Kupfer, First, & Regier, ; Widiger et al, ). For example, now the DSM‐5 proposes an alternative model of personality disorder, which stresses the coexistence of pathological personality traits, and ICD‐11 also underlines that the intensity of symptoms must be considered (Gaebel, Zielasek, & Reed, ).…”
Section: Introductionmentioning
confidence: 99%